Operationalization of Excessive Masturbation—Development of the EMS. Issue 2 (3rd July 2018) - Driemeyer, Wiebke; Snagowski, Jan; Laier, Christian; Schwarz, Michael; Brand, Matthias
Abstract: Research has recently focused on hypersexual behavior and Internet-pornography-viewing disorder as potential psychopathological conditions, but specific aspects of the phenomena have been widely neglected. This study aimed to investigate excessive masturbation as a subset and symptom of hypersexual behaviors. 2 studies with independent samples have been conducted. In study 1 ( n  = 146), the Excessive Masturbation Scale (EMS) was designed and tested via explorative factor analysis. In study 2 ( n  = 255), the psychometric properties of the EMS were evaluated by confirmatory factor analysis. A replicable 2-factor structure ("Coping" and "Loss of Control") was identified. The EMS showed good psychometric properties and provides a promising basis for further research.